Assessing hydropower flexibility for integrating solar and wind energy in West Africa using dynamic programming and sensitivity analysis. Illustration with the Akosombo reservoir, Ghana. (10th March 2021) - Danso, Derrick Kwadwo; François, Baptiste; Hingray, Benoit; Diedhiou, Arona
Abstract: The flexibility of hydropower plants with large reservoirs is frequently exploited to integrate large shares of variable and intermittent renewable energy sources in electricity systems. In this study, we assess the flexibility that could be provided by large hydropower reservoirs in West Africa to cope with planned future solar and wind energy generation in the region. Reservoir operations are estimated via Dynamic Programming with the objective to minimize the variability of the residual demand that commonly needs to be supplied by conventional generation means at high monetary and carbon costs. The analysis framework is demonstrated for the Akosombo hydropower reservoir in Ghana for which a number of future scenarios of increased electricity demand are considered. Different combinations of solar and wind energy development are considered to match the increase in demand. The results show that the Akosombo hydropower reservoir can smooth out the variability of the residual electricity demand when the increase in electricity demand is below 25% and the corresponding contribution of solar and wind energy to the total electricity generation does not exceed 20%. For larger increases in demand and thus larger solar and wind generation, the Akosombo reservoir cannot fully smooth-out the variability of the subsequent residual demand, although, the performance varies with the relative contribution of solar and wind in the energy mix. However, we found that the use of an additional short-term storage helps to further reduce the variability of the residual demand. Highlights: For the first time, acceptable S&W integration levels in Ghana is shown. Dynamic programming is used for flexible hydropower operations to integrate S&W. A 20% penetration of S&W can be fully integrated by flexible hydropower operations. A S&W ratio of 1:3 minimizes residual demand variability for higher penetrations. The extra storage strongly influences residual demand in solar-dominated mixes.